ANALISIS MINAT BELI HALAL BRANDING SKINCARE - Khairunnisa Permata Sari (2020)
This study examines people's buying interest in Safi's skincare products. The purpose of this research is to find out what influences people's buying interest towards Safare sincare products, this research covers halal branding, non-celebrity endorsers and brand trust. The approach used in this research is descriptive. The type of data used in this study is quantitative data and uses primary and secondary data sources. The sample used in this study amounted to 100 people with simple random sampling technique. This data collection uses a questionnaire. Data analysis techniques were processed using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). The results of data analysis show that: (1) halal branding does not affect buying interest with a tcount of 1.774 <ttable 1.985 and a significant value of 0.077> 0.05; (2) halal branding has a significant positive effect on brand names with a value of 5.594> t table 1.985 and a significant value of 0.000 <0.05; (3) non-celebrity endorsers have a positive effect on buying interest with a tcount of 3.480> t table 1.985 and a significant value of 0.001 <0.05; (4) non-celebrity endorsers have a positive effect on brand trust with a tcount of 3.984> t table 1.985 and a significant value of 0.000 <0.05; (5) brand trust has a positive effect on buying interest with a tcount of 7.932> t table 1.985 and a significant value of 0.000 <0.05. Obtained R-square value of the Brand Trust variable that is equal to 0.675. The R-square value of the Buy Interest variable is 0.763.